Protective role of genistein in acute liver damage induced by carbon tetrachloride - Kuzu, Nalan; Metin, Kerem; Dagli, Adile Ferda; Akdemir, Fatih; Orhan, Cemal; Yalniz, Mehmet; Bahcecioglu, Ibrahim Halil (My University, 2007)
Aim. In the present study, we investigated the protective effect of genistein in experimental acute liver damage induced by CCl4. Method. Forty rats were equally allocated to 5 groups. The first group was designated as the control group (group 1). The second group was injected with intraperitoneal CCl4 for 3 days (group 2). The third group was injected with subcutaneous 1 mg/kg genistein for 4 days starting one day before CCl4 injection. The fourth group was injected with intraperitoneal CCl4 for 7 days. The fifth group was injected with subcutaneous 1 mg/kg genistein for 8 days starting one day before CCl4 injection. Plasma and liver tissue malondialdehyde (MDA) and liver glutathione levels, as well as AST and ALT levels were studied. A histopathological examination was conducted.Results. Liver tissue MDA levels were found significantly lower in group 3, in comparison to group 2 ( P<.05). Liver tissue MDA level in group 5 was significantly lower than that in group 4 ( P<.001) .Liver tissue glutathione levels were higher in group 5 and 3, relative to groups 4 and 2, respectively ( P>.05 for each). Inflammation and focal necrosis decreased in group 3, in comparison to group 2 ( P<.001 for each). Inflammation and focal necrosis in group 5 was lower than that in group 4 ( P<.001). Actin expression decreased significantly in group 5, relative to group 4 ( P<.05).Conclusion. Genistein has anti-inflammatory and antinecrotic effects on experimental liver damage caused by CCl4. Genistein reduces liver damage by preventing lipid peroxidation and strengthening antioxidant systems. Copyright © 2007 Nalan Kuzu et al.
Keywords: Acute Disease; Animals; Antioxidants; Carbon Tetrachloride; Female; Genistein; Glutathione; Immunohistochemistry; Injections, Intraperitoneal; Injections, Subcutaneous; Lipid Peroxidation; Liver; Liver Diseases; Malondialdehyde; Protective Agents; Rats; Rats, Sprague-Dawley; Rattus; actin; alanine aminotransferase; aspartate aminotransferase; carbon tetrachloride; genistein; glutathione; malonaldehyde; antioxidant; carbon tetrachloride; genistein; glutathione; malonaldehyde; protective agent; alanine aminotransferase blood level; animal experiment; animal model; antiinflammatory activity; article; aspartate aminotransferase blood level; blood level; control group; controlled study; disease severity; drug effect; female; histopathology; inflammation; lipid peroxidation; liver injury; liver level; liver necrosis; liver protection; nonhuman; priority journal; protein expression; rat; statistical significance; acute disease; animal; blood; chemically induced disorder; immunohistochemistry; intraperitoneal drug administration; liver; liver disease; metabolism; pathology; Sprague Dawley rat; subcutaneous drug administration